The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1113/jphysiol.1990.sp018035
|View full text |Cite
|
Sign up to set email alerts
|

The renal and vascular effects of central angiotensin II and atrial natriuretic factor in the anaesthetized rat.

Abstract: SUMMARY1. The interaction between atrial natriuretic factor (ANF) and angiotensin II (Ang II) within the brain to influence renal function and blood pressure was studied in Inactin-anaesthetized male Sprague-Dawley rats.2. Central infusion of ANF produced a diuresis which was associated with a significant decrease in plasma arginine vasopressin (AVP) level. There was no change in sodium excretion rate over the 80 min of intracerebroventricular ANF infusion and ANF produced no detectable change in mean arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In several studies it was postulated that ANP acts in the brain by partially inhibiting the angiotensin II (ANG II) pathway. ANP injection prevented the pressor effect of centrally administered ANG II ( 46 , 51 ). On the behavioral level, centrally administered ANP was shown to inhibit water intake induced by ANG II or dehydration in rats ( 55 ).…”
Section: Natriuretic Peptidesmentioning
confidence: 93%
See 1 more Smart Citation
“…In several studies it was postulated that ANP acts in the brain by partially inhibiting the angiotensin II (ANG II) pathway. ANP injection prevented the pressor effect of centrally administered ANG II ( 46 , 51 ). On the behavioral level, centrally administered ANP was shown to inhibit water intake induced by ANG II or dehydration in rats ( 55 ).…”
Section: Natriuretic Peptidesmentioning
confidence: 93%
“…Numerous studies found no change in BP upon central administration of ANP ( 48 52 ) or BNP ( 53 ). However, there are reports describing a decrease in vasopressin secretion following central ANP infusion, suggesting that ANP and vasopressin may interact to attenuate the central pressor effects of vasopressin ( 49 , 51 54 ). Pretreatment of rats with i.c.v.…”
Section: Natriuretic Peptidesmentioning
confidence: 99%
“…Furthermore, central injection of AT 1 receptor antagonist, Losartan, blocks AT 1 receptors and influences on central angiotensin mechanisms [24,26]. Infusion of Ang II into a lateral cerebral ventricle produce an increase in blood pressure [27,20,28], increase in mean arterial pressure [29,30], decrease in urine flow [27], regulate hydromineral balance [22], induce the pressor response [31], stimulate AVP and OT release [20,28] and elevate RSNA (renal sympathetic nerve activity) [32]. Losartan blocks water intake in intracellular and extracellular dehydrated conditions, inhibits the release of AVP and OT, reduces RSNA response and antidiuretic action [5,32].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the important cardio-renal function of NPs, they also have vasorelaxant effects and they inhibit the renin–angiotensin-aldosterone system (RAAS) and the sympathetic nervous system (SNS) [ 108 , 109 ]. Circulating ANP and vasopressin can interact to attenuate the central pressor effects of vasopressin [ 36 , 110 , 111 , 112 , 113 , 114 ], and brain natriuretic peptide (BNP) suppresses the secretion of vasopressin [ 104 ]. All of these brain regions participate in the regulation of mood and CV responses.…”
Section: Psychiatric and Cardiometabolic Mediators That Could Be Umentioning
confidence: 99%